Determinants of conversion during laparoscopic cholecystectomy among a sample of Iraqi patients - Alluaibi, Abutalib B.; Hassan, Bahaa K.; Ali, Alaa H.; Muhsen, Ahmed A. (International Surgery Journal, 2018)
Background: Laparoscopic cholecystectomy has become a standard technique for gall bladder surgery of symptomatic cholelithiasis. However, conversion to open cholecystectomy is sometimes necessary. The aim of the present study was to assess the predictive factors that increase the possibility of conversion of laparoscopic cholecystectomy to open cholecystectomy. Methods: A total of 621 laparoscopic cholecystectomies were attempted at AL-Mawanee General Hospital and AL-Sader Teaching Hospital in Basrah, IRAQ from June 2012 till June 2016.Of these,43 had to be converted to open cholecystectomies. Patients assessed according to different factors, including age, sex, acute cholecystitis, adhesions of gallbladder and calot’s triangle, obesity, previous abdominal surgery, anatomical variation of gallbladder and Calot’s triangle and intraoperative complications (bleeding, bile duct injury, visceral injury). Results: Conversion to open cholecystectomy was performed in 43 patients (6.92%). The significant factors for conversions were adhesions of gallbladder and Calot’s triangle(39.53%) followed by acute cholecystitis(34.88%). Rate of conversion in other factors are as the following i.e., isolated male gender (0%), age (0%), previous abdominal surgery (9.3%), obesity (2.33%), anatomical variations of gall bladder and calot’s triangle (2.33%), intra operative complications including bleeding (4.65%), bile duct injury (4.65%), visceral injury (2.33%) were insignificant factors for conversion. Conclusions: Adhesions of gallbladder and calot’s triangle is the most common predictive factor and cause for conversion from laparoscopic cholecystectomy to open cholecystectomy. Acute cholecystitis found to be the strongest factor for conversion despite its incidence is lower than adhesions of gall bladder and calots triangle. Male gender and age more than fifty years are not direct predictive factors for conversions.